Microdialysis Sampling Coupled to Microchip Electrophoresis with Integrated Amperometric Detection on an All Glass Substrate - Scott, David E. (2013)
The development of an all-glass separation-based sensor using microdialysis coupled to microchip electrophoresis with amperometric detection is described. The system includes a flow-gated interface to inject discrete sample plugs from the microdialysis perfusate into the microchip electrophoresis system. Electrochemical detection was accomplished with a platinum electrode in an in-channel configuration using a wireless electrically isolated potentiostat. To facilitate bonding around the in-channel electrode, a fabrication process was employed that produced a working and a reference electrode flush with the glass surface. Both normal and reversed polarity separations were performed with this sensor. The system was evaluated in vitro for the continuous monitoring of the production of hydrogen peroxide from the reaction of glucose oxidase with glucose. Microdialysis experiments were performed using a BASi loop probe with an overall lag time of approximately five minutes and a rise time of less than 60 seconds.